THE DEVELOPMENT OF SCIENCES IN AL-QUR'AN PERSPECTIVES - Soleha Soleha; Adrian Adrian (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
This research applied the method of interpretation and bi ’l-ra'y approach. It tried to reinvent the spirit of the Qur'an and Hadith to push humankind to develop science integratively and to make it beneficial for human beings and nature. The research confirmed that human beings as khalīfah fi ’l-arḍ, was given the right and freedom to explore what is on this earth and its contents with all its potential. Even in the Qur'an, Allah has made available all materials for the development of science, al ayah al-kawniyyah verses. Al-Qur'an as a resource of knowledge in Islam stated that one of the advantages human beings from the others is that they were endowed reason to search and explore science for the progress of human beings.